Retreatment with intravenous immunoglobulin (IVIG) of refractory Guillain Barre syndrome in children - Rivas Larrauri Francisco; Dávila Gutiérrez Guillermo (Instituto Nacional de Pediatría, 2014)
Guillain-Barré syndrome (GBS) is an acute symmetrical pa- ralyzing disease due to a demyelinating polyrradiculoneuropathy, often induced by a preceding infection 1. The main modalities for the treatment of GBS include plasmapheresis and intrave- nous immune globulin. Reports of the use of IVIG in children with GBS are limited: 1 g/kg for two days or 400 mg/kg for five days. While these studies in children are not definitive because of design limitations, their results are consistent with the larger randomized trials in adults 2,3.